STEM-based e-module on excretory system to enhance high school students’ critical thinking and independence - Eko Sucipto; Kartika Ratna Pertiwi (University of Muhammadiyah Malang, 2025)
Enrichment programs are important for maximizing capabilities and improving mastery skills 21st century, however, their implementation does not maximize the material system excretion. STEM (Science, Technology, Engineering, Mathematics)-based electronic module (e-module) have become a choice for increasing mastery skills in the 21st century and quality enrichment programs. This research aims to develop a STEM-based e-module for an enrichment program on excretory system material that is valid, practical, and effective to improve critical thinking skills and learning independence. This study was designed as a research and development using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. This research uses a simple random sampling technique with subjects originating from 5 classes XI IPA of SMAN 1 Wonosari in Gunungkidul Regency, Yogyakarta Province, which have exceeded the minimal achievement criteria on excretory system material. The research instruments included validation sheets for media and material experts, student and teacher response questionnaires, test instruments for critical thinking skills, and assessment questionnaires for independent study. The technique of the data analysis used descriptive analysis and the MANOVA test. The results of validation by material experts obtained a score of 3.79, while by media experts obtained a score of 3.81, indicating the validity category is